IDEOLOGIES OF BELONGING AND IDENTITY AND THEIR IMPLICATIONS FOR THE FORMATION OF IRAQI AUTHORITY - Hussein Ali Hussein (Galaxy International Interdisciplinary Research Journal, 2023)
In Iraq, cultural and intellectual diversities exacerbate the disparity between Iraqi sects, as this intellectual and cultural gap has been developing for years. The Iraqi government can develop a justified policy and ideology of exclusion and fragmentation of identity according to the interests of the authority, exploiting this gap and its conflicts. This closed ideology contains rules and ideas that lead to the denial of reality and the elimination of the different sects. It is difficult to isolate this phenomenon from the ideological, cultural, political, social and religious conflicts within the state. This case depicts that the ideological violence practiced in Iraq historically was based on what we called the “dynamic doctrine,” inherited in the social and political subconscious, and was also supported by factors of religious, political, and social upbringing. This justifies physical political violence. It is preceded by ideological processes practiced by elements of the moral state to achieve equality and freedom - from a governmental standpoint - between sects and to reach unity through mixing. This formed an Iraq with divided and warring identities according to complex details that combined religious, political, social and cultural memory. Thus, societal dynamics became driven by subjective factors and past psychological motives. This appeared through the conflict of representative memory in post-2003 Iraq, under the pretext of entitlement, and from here the Iraqi memory was divided. To an unjust and oppressed memory; That is, the exchange of roles between the two memories, which means that there is a defect in the warring and intertwined pluralistic systems that prevent the transformation from an entity to a political entity, meaning that there is a fear of future tyranny. Therefore, the democratic transformation in post-2003 Iraq requires rebuilding the artificial memory according to methodologies and concepts based on common interests.